SOCIAL JUSTICE AND THE QUR'ANIC PERSPECTIVE: A STUDY OF THE SOCIAL IMPLICATIONS OF THE QUR'ANIC VERSES - Jefri Geovani; Tera Saputra (STAI Sebelas April Sumedang, 2023)
Abstract This study examines the concept of social justice as presented in the Qur'an, focusing on its implications for modern social policies. Using a qualitative approach, the research analyzes key Qur'anic verses such as Surah Al-Baqarah (2:177), An-Nisa’ (4:58), and Al-Hujurat (49:13), alongside classical and contemporary tafsir. The study employs thematic analysis to explore how the Qur'anic principles of justice, equality, and wealth distribution can be applied in addressing contemporary issues such as economic inequality, gender justice, and governance. The research finds that the Qur'an offers a comprehensive framework for creating a more equitable society, with potential applications in modern public policy. It concludes that Islamic values provide relevant guidance for fostering social welfare and reducing disparities in Muslim-majority countries. Future studies could expand on the practical integration of these principles in contemporary governance systems.